The 2014 European Parliament elections in Southern Europe: second-order or critical elections? - Schmitt, H. (2015)
The article provides a comparative analysis of the 2014 European Parliament elections across the six countries of Southern Europe by gauging the performance of the second-order election model. Both the aggregate hypotheses of this model and evidence of micro-level foundations are analysed. The findings reveal that the political and electoral consequences of the economic crisis have not drastically challenged the second-order character of these elections in Southern Europe. However, electoral behaviour also exhibits some indications of a more critical contest.